2001
DOI: 10.1111/j.1469-7793.2001.0195g.x
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic response to β‐adrenergic receptor stimulation and anti‐adrenergic effect of ACh in endothelial NO synthase‐deficient mouse hearts

Abstract: It is well established that NO released from the endothelium plays an important role in the regulation of vascular tone. This was most stringently demonstrated by the generation of mice deficient in endothelial NO synthase (eNOS), which develop hypertension (Huang et al. 1995;Shesely et al. 1996;Gödecke et al. 1998). Besides its role in the regulation of organ perfusion, NO might also modulate cardiac function (for review see Kelly et al. 1996). The cytokine-mediated depression of cardiac contractility has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 36 publications
10
85
2
1
Order By: Relevance
“…In particular, Gyurko et al 24 found an enhanced maximal LV dP/dT in response to ␤-adrenergic stimulation in NOS3 Ϫ/Ϫ mice in both in vivo-perfused and Langendorff-perfused hearts, whereas others, using the same model, found no change either in calcium current or papillary muscle contractility. 4 Godecke et al, 25 using a differently generated NOS3 Ϫ/Ϫ mouse, also found a greater maximal LV dP/dT in response to dobutamine in isolated hearts. Differences in experimental conditions and preparations might have been in part responsible for the reported inconsistency in experimental findings (see review 3 ).…”
Section: Nos1 and ␤-Adrenergic Inotropic Effectmentioning
confidence: 99%
“…In particular, Gyurko et al 24 found an enhanced maximal LV dP/dT in response to ␤-adrenergic stimulation in NOS3 Ϫ/Ϫ mice in both in vivo-perfused and Langendorff-perfused hearts, whereas others, using the same model, found no change either in calcium current or papillary muscle contractility. 4 Godecke et al, 25 using a differently generated NOS3 Ϫ/Ϫ mouse, also found a greater maximal LV dP/dT in response to dobutamine in isolated hearts. Differences in experimental conditions and preparations might have been in part responsible for the reported inconsistency in experimental findings (see review 3 ).…”
Section: Nos1 and ␤-Adrenergic Inotropic Effectmentioning
confidence: 99%
“…The observed effects of NOS3 signaling on the ␤-AR response are the opposite of NOS1 (30), that is, studies have shown that NOS3 signaling depresses the functional response to ␤-AR stimulation. For example, mice with specific knockout of NOS3 (NOS3 Ϫ/Ϫ ) have an increased response to ␤-AR stimulation (4,11,19,20,47). Similarly, transgenic mice with cardiac myocyte-specific NOS3 overexpression have a decreased response to ␤-AR stimulation (9,23).…”
mentioning
confidence: 99%
“…The molecular basis for muscarinic inhibition of cardiac contractility is controversial. 1,2 Activation of NO synthase III leading to an increase of the cGMP level has been reported to contribute to muscarinic inhibition 3-5 as well as the irrelevance of NO, 6 NO synthase III,7,8 and cGMP/cGMPdependent protein kinase I (cGKI) 9 for this signaling pathway. The cGMP receptor potentially mediating the negative inotropic effect has not been identified.…”
mentioning
confidence: 99%